Evaluation of The Effect of Epidural Steroid Injection on Interleukin -18 in Patients with Low Back Pain - Alqaseer, Zainab R.; Alzamily, Ajil; alsalman, Ihsan (Journal of Biomedicine and Biochemistry, 2022)
Background: Having lower back discomfort is common. Back ten- sion may cause sciatica. Low back, or lumbar region, begins below the ribs. Most people will have low back discomfort. Disk damage, struc- tural issues, and atherosclerosis also contribute. Rest, physical ther- apy, and medicine relieve pain. Weight management and exercise re- duce low back pain risk. Epidural steroids alleviate leg and back pain (ESIs). Their extensive history makes them a good nonsurgical sciat- ica and back pain treatment. ESI may relieve radiculopathy.Human interleukin-18 (IL18) is an interferon-gamma-inducing factor. Gene generates inflammatory cytokine. The Aim: The study was aimed at the effect of epidural steroid in- jection on the concentrations of IL-18 in patients with LBP. Materials and Methods: Serum Interleukin-18 was measured us- ing Elabscience® kits. In a case-control study, 36 healthy people and 22 LBP patients (13 men and 9 women) were compared (23 males and 13 females). Our research included 30 to 79-year-olds. All patients in this research were diagnosed by specialists based on their histo- ries and clinical features. A patient’s file includes ages, genders, fam- ily history, ailments (such as diabetes and hypertension), medicines, weight, height, and BMI (BMI). Participants with COVID-19, autoim- mune disorders, diabetes mellitus, acute or chronic liver disease, renal disease, thyroid function abnormalities, or kidney disease were elim- inated. Results: Interleukin-18 (IL-18) was substantially greater in patients with LBP (250.87 ±29.72 pg/mL) than following injection and con- trol (157.94± 47.23), (132.40 ±22.58) pg/mL, respectively. Our inves- tigation found a very significant difference (p-value < 0.0001) in IL- 18 concentrations compared to L Also, mean values before and after injection were significantly different (p-value 0.0001). There is a sig- nificant difference in mean values before and after injection (p-value < 0.0001) and after injection and control (p = 0.0012). Conclusion: Epidural steroid treatment positively impacts LBP patients by decreasing IL-18 levels, which could be played an essential role in repairing damaged tissues.